Mental Illness in Children and Adolescents: A Rising Concern on College Campuses. Issue 4 (July 2018) - Beal, Judy A.
Abstract : Mental health issues such as anxiety and depression are becoming more common among children and adolescents. Our pediatric nurse expert, Dr. Beal, discusses the latest statistics on prevalence and offers suggestions for promoting optimal mental health for the pediatric population.